What factors drive trust in police after civil wars: the case of Colombia - Branton, Regina P. (International journal of comparative and applied criminal justice, 2024)
We know that civil wars have negative and long-term consequences for public trust in state institutions. However, few studies have examined the post-peace challenges of rebuilding trust in state institutions. In this study, we utilise the case of Colombia to explore the impact of civil wars on the institutional trust of the police. We find that perspectives on abuse, punishment, and corruption are significant predictors of trust in the Colombian police. Further, we find that when we test all three phenomena together, perceptions of police abuse and experience with bribery are the key drivers of trust of police in Colombia.